Profil gelatinisasi formula pempek âlenjerâ - Karneta, Railia; Rejo, Amin; Priyanto, Gatot; Pambayun, Rindit (Balai Riset dan Standardisasi Industri Palembang, 2014)
This research aims to determine the gelatinization profiles of pempek lenjer dough from several formulas, with comparising fish with tapioca flour treatment. During the heating occured an increase in viscosity caused by the swelling of the irreversible starch granules in the water caused by the kinetic energy of water molecules which is stronger than the attraction of starch molecules so that the water could get into the starch granules. Gelatinization profile result showed that the higher the addition of tapioca flour on the pempek dough the lower the initial gelatinization temperature (63Â°C), the lower the maximum viscosity (100 BU) is more compact the gel, paste stability was relatively low (41 BU) and the higher the reverse viscosity (31 BU), the development of the granules became larger, but the greater the the possibility of retrogradation.Keywords: dough, formulation, gelatinization, amilography properties, pempekAbstrakPenelitian ini bertujuan untuk mengetahui profil gelatinisasi adonan pempek lenjer dari beberapa formula, dengan perlakuan perbandingan ikan dengan tepung tapioka. Selama pemanasan terjadi peningkatan viskositas yang disebabkan oleh pembengkakan granula pati yang irreversible dalam air, karena energi kinetik molekul air lebih kuat dari daya tarik molekul pati sehingga air dapat masuk ke dalam granula pati. Hasil profil gelatinisasi menunjukkan bahwa semakin tinggi penambahan tepung tapioka pada adonan pempek maka suhu awal gelatinisasi semakin rendah (63Â°C), viskositas maksimum semakin rendah (100 BU) gel lebih kompak, stabilitas pasta relatif rendah (41 BU) dan viskositas balik semakin tinggi (31 BU) pengembangan granula lebih besar, tetapi kemungkinan retrogradasi semakin besar.Kata kunci: adonan, formula, gelatinisasi, sifat amilografi, pempek